RET fusion in advanced non-small-cell lung cancer and response to cabozantinib: A case report. Issue 3 (January 2019) - Wang, Yucong; Xu, Yinghui; Wang, Xu; Sun, Chao; Guo, Ye; Shao, Guoguang; Yang, Zhiguang; Qiu, Shi; Ma, Kewei
Abstract: Rationale: Lung cancer is a series of gene-driven disease. EGFR, ALK, and ROS1 are 3 major driver genes that play an important role in lung cancer development and precision management. Additionally, rare genetic alterations continue to be discovered and may become novel targets for therapy. The RET gene is one of such rare genetic alteration of non-small cell lung cancer (NSCLC). In this report, we present a RET-positive case that benefited from cabozantinib treatment. Patient concern: A 50-year-old male patient was diagnosed with lung adenocarcinoma 2 years ago, at that time he received palliative surgery of pulmonary carcinoma and completed 4 cycles of chemotherapy with gemcitabine and cisplatin. Six months later, he was hospitalized in our cancer center due to the disease recurrence, presenting with pleural metastasis. Diagnosis: Gene alteration was examined using the intraoperative specimen by PCR method, and KIF5B/RET gene fusion was detected. Therefore, the patient was diagnosed with late-stage lung adenocarcinoma with RET gene mutation. Interventions: The patient received treatment with cabozantinib from June 2017. Outcomes: Cabozantinib was administered (140 mg orally, once daily) for approximate 9 months, and his disease achieved stable disease (SD). During that period, there were no severe adverse events (AE), except for a grade II rash (CTCAE 4.0). Lessons: We found that the RET fusion gene is a novel driver molecular of lung adenocarcinoma in patients without common mutations in such genes as EGFR, ALK, and ROS1 . This case report supports a rationale for the treatment of lung adenocarcinoma patients with a RET fusion and provides alternative treatment options for these types of NSCLC patients.